2019
DOI: 10.1016/j.ijrobp.2019.06.2061
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Prognosis of Radiotherapy for Hepatocellular Carcinoma with Tumor Thrombosis in Main Portal Vein or/and Vena Cava

Abstract: trial studies combination transarterial chemoembolization (TACE) and Stereotactic Body Radiation Therapy (SBRT) for BCLC A patients with HCC from 4-7 cm. Materials/Methods: Patients were eligible if they were BCLC A, Child-Pugh score 7, had a single HCC from 4-7 cm, no evidence of macrovascular invasion, no evidence of metastatic disease, ECOG 0, and were not suitable for resection or liver transplantation. Treatment consisted of drug-eluting bead (DEB)-TACE at time 0 and 1 month followed by SBRT completed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the current study, we showed similar results with the previous studies. Compared with group B (IMRT alone), group A (IMRT plus sorafenib) displayed a favorable trend in median OS (11.0 versus 9.0 months, P � 0.036), 1 yr and 2 yrs OS (44.9% versus 28.6% and 3.8% versus 2.6%), median PFS (6.0 Recently, Chen et al [23] analyzed sixty-one HCC patients with tumor thrombosis in the main portal vein or vena cava to assess the response and survival of radiotherapy. In the study, the tumor thrombosis exhibited a higher response rate than the primary tumor (83.7% versus 77.1%) in the field of radiotherapy, while the primary failure pattern was the outfield progression.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, we showed similar results with the previous studies. Compared with group B (IMRT alone), group A (IMRT plus sorafenib) displayed a favorable trend in median OS (11.0 versus 9.0 months, P � 0.036), 1 yr and 2 yrs OS (44.9% versus 28.6% and 3.8% versus 2.6%), median PFS (6.0 Recently, Chen et al [23] analyzed sixty-one HCC patients with tumor thrombosis in the main portal vein or vena cava to assess the response and survival of radiotherapy. In the study, the tumor thrombosis exhibited a higher response rate than the primary tumor (83.7% versus 77.1%) in the field of radiotherapy, while the primary failure pattern was the outfield progression.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, other studies included in the present meta-analysis were more favorable for the application of combination therapy. In terms of toxicities, comparative studies did not report excessive serious toxicities related to the concurrent application [20,21,35,[38][39][40], and single-arm studies reported that the degree of complication was acceptable and severe toxicity (grade ≥4) was rare [19,36,37]. Furthermore, Zhang et al [39] reported that the concurrent application of brachytherapy to the portal vein significantly reduced symptoms due to liver compensation.…”
Section: Discussionmentioning
confidence: 99%
“…The abstract screening was performed on 295 studies, and a full-text review was performed on 47 studies after excluding 248 studies with irrelevant subjects or formats. A full-text review was performed to identify studies that fully met the inclusion criteria, and 11 studies were finally included in the present study [16,[18][19][20][21][35][36][37][38][39][40]. The selection process is illustrated in Figure 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation